Investigating the kinetics of repeated sprint ability in national level adolescent hockey players - Runacres, A.; Mackintosh, K. A.; McNarry, M. A. (Journal of Sports Sciences, 2023)
Repeated sprint ability (RSA) is more closely related to match performance outcomes than single-sprint performance, but the kinetic determinants in youth athletes remain poorly understood. Therefore, the aim of the study was to explore the kinetic determinants of RSA in youth athletes. Twenty trained adolescents (15 girls; 14.4 ± 1.0 years) completed five 15 m repetitions interspersed with 5-s rest. Velocity was measured during each trial using a radar gun at >46 Hz, following which the force-velocity-power (F-v-P) profile was fitted to a velocity-time curve and instantaneous power and force variables calculated. The mechanical efficiency of force application (DRF) was the primary predictor of both single and repeated sprint performance in adolescents. Secondly, hierarchical analyses revealed the percentage reduction in peak velocity, DRF, and allometrically scaled peak force explained 91.5% of the variance in 15 m sprint time from sprints 1-5. Finally, declines in allometrically scaled peak power were more closely related to declines in peak force than reductions in velocity. In conclusion, given DRF was the primary predictor of both single and repeated sprint performance training programmes targeting RSA need to include technique, and skill acquisition, components.